Depression and suicidality in psoriasis: review of the literature including the cytokine theory of depression. (9th August 2017) - Koo, J.; Marangell, L.B.; Nakamura, M.; Armstrong, A.; Jeon, C.; Bhutani, T.; Wu, J.J.
Abstract: Psoriasis can be a socially isolating disease due to debilitating physical symptoms and the stigma patients feel because of the appearance of their skin. Mental health comorbidities such as anxiety, depression and suicidal ideation and behaviour (SIB) are prevalent in patients with psoriasis. Patients with mild psoriasis can experience psychiatric comorbidities; however, disorders such as depression and SIB are more common in patients with severe psoriasis or psoriatic arthritis. Psychiatric disorders can both result from and contribute to progression of psoriasis, suggesting that psoriasis and psychiatric conditions, such as depression, may have overlapping biological mechanisms. Proinflammatory cytokines such as interleukin (IL)‐1 and IL‐6 are elevated in both psoriasis and depression, indicating that the inflammatory process may be involved in the progression of both diseases. Elevated cytokine levels in the central nervous system cause physiologic and biochemical changes that may contribute to the development of depression. In this review of the literature, we discuss the evidence that supports the association of psoriasis with mental health disorders and the tools used to detect the presence of these comorbidities. Additionally, we review the most prominent hypotheses on the mechanisms by which the inflammatory response and elevated cytokines can cause depression. These results highlight the role that systemic inflammation plays in the various mental health comorbidities associated with psoriasis, including depression and SIB.